Comparative Evaluation of Microscopy and Culture Methods in the Diagnosis of Pulmonary Tuberculosis in HIV Infected Patients - Praveen C. Shetty; Gopalkrishna Bhat K (Journal of Pure and Applied Microbiology, 2017)
Tuberculosis is a serious infectious disease with considerable public health problem due to its person to person transmission, morbidity and mortality. To evaluate the performance of different laboratory methods such as direct microscopy, concentration methods and culture in the diagnosis of pulmonary tuberculosis in HIV infected patients. Sputum samples were collected using standard procedure. For each sputum sample, four smears were prepared, one direct smear, second after processing by Petroff’s method, third by NALC-NaOH method and fourth after processing by Sodium hypochlorite method. Ziehl Neelsen (ZN) staining was done on these smears using standard techniques. Deposit obtained after processing by Petroff’s method and NALC-NaOH method were inoculated on to Lowenstein Jensen (LJ) medium and Middlebrook’s 7H11 agar medium. A total of 75 HIV infected patients presenting with symptoms of pulmonary tuberculosis were included in the study. 11 (14.6%) were direct sputum smear positive and 13 (17.3%) were AFB positive after concentration and culture positive. Out of 139 sputum samples tested, 22 (15.8%) were positive in direct smear. 25 samples, (18%) were positive for AFB after concentration and culture. We conclude that concentration methods are sensitive and reliable in the diagnosis of pulmonary TB in HIV infected patients. Sodium hypoclorite and Petroff’s concentration methods are simple, cost effective and reliable provided centrifugation is done at 3800xg. Culture methods are sensitive and specific but take time for growth of M. tuberculosis (4-6 weeks).